Solo Exhibition-Recent Acquisitions, Pierides Museum, Larnaka - Antoniou, Klitsa (My University, 2026)
Solo Exhibition-Recent Acquisitions, Pierides Museum, Larnaka, Cyprus. Curated by Marina Bryonidou